Bioproperties, Nanostructured System and Analytical and Bioanalytical Methods for Determination of Rapamycin: A Review. (4th July 2022) - dos Santos, Karen Cristina; dos Reis, Leidiana Rocha; Rodero, Camila Fernanda; Sábio, Rafael Miguel; Junior, Alberto Gomes Tavares; Gremião, Maria Palmira Daflon; Chorilli, Marlus
Abstract: The drug rapamycin is a potent inhibitor of the mTOR complex, acting directly in the signaling cascade of this protein complex; interrupting cell proliferation, in addition to being an extremely efficient immunosuppressant. Currently this drug is being used in several types of cancer. Rapamycin has been a target of great interest within nanomedicine involving nanostructured systems for drug delivery aiming to increase the bioactivity and bioavailability of this drug. In addition, there is a constant search for analytical methods to identify and quantify this drug. Numerous high-performance liquid chromatography analytical techniques, mass spectrometry and immunoassay techniques have been employed efficiently in an attempt to develop increasingly sensitive analytical methods. Thus, this review sought to bring together current and relevant scientific works involving rapamycin and; besides analytical methods more used for quantification of this molecule.